Feedgoals the presentation of the self on instagram - Carim, Christine Ann Angela G. (2018)
The digital age paved the way for a new environment for self-presentation. Research suggests that self-representation through social media profiles show a dissimilarity on offline interactions. (Lindahl and Ohlund, 2013). Individuals therefore use this advantage to manipulate and manage the impressions they can get. Thus, the researcher applied the Impression Management Theory as presented in Goffman?s (1959) book, Presentation of the Self in Everyday Life. Having Instagram as the medium for communication of impression management online, ten users of the social networking app were interviewed for this research. Results suggest that participants have been influenced by several factors circulating in the competitive online world such as the compliance to new trends, updates, and features. By the end of the study, it was also concluded that it need not matter whether the participants? online self is similar to their offline self. The self they presented online becomes their hyperreal selves, real or not real, as a product of online self-commodification.